Management of School Guidance and Counseling Teachers in Addressing Student Delinquency at State Islamic Junior High School 2 Purwakarta - Asep Saepul Muslim (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze and describe the management role of Guidance and Counseling (BK) teachers in addressing student delinquency at Madrasah Tsanawiyah Negeri 2 Purwakarta. Student delinquency in madrasah environments is a serious issue that significantly impacts the quality of education and the character development of students. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. Research informants included BK teachers, the madrasah principal, homeroom teachers, and involved students. Data analysis followed three interactive stages: data reduction, data presentation, and conclusion drawing. The findings reveal: (1) The management role of BK teachers at MTsN 2 Purwakarta is implemented through preventive actions including classical guidance, preservative actions directing students toward positive extracurricular activities, and curative actions including individual counseling and heart-to-heart communication; (2) Steps taken by BK teachers encompass personal approaches, categorization of delinquency types, provision of information services, group counseling, group guidance, and parental involvement for severe cases; (3) Obstacles faced by BK teachers include students' low self-awareness, unsupportive family backgrounds, and insufficient parental cooperation. This research affirms the importance of collaboration between BK teachers, homeroom teachers, school principals, and parents in shaping students' positive behavior.